2018
DOI: 10.1038/s41598-018-21784-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Serum Phosphate Levels and Low Muscle Strength, Dynapenia, and Sarcopenia

Abstract: Emerging evidences addressed an association between phosphate and muscle function. Because little attention was focused on this issue, the objective of our study was to explore the relationship of phosphate with muscle strength, dynapenia, and sarcopenia. From the National Health and Nutrition Examination Survey, a total of 7421 participants aged 20 years or older were included in our study with comprehensive examinations included anthropometric parameters, strength of the quadriceps muscle, and appendicular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 49 publications
4
27
1
1
Order By: Relevance
“…On the other hand, hyperphosphatemia may contribute to the development of muscle weakness and frailty, at least in patients with CKD [ 335 , 336 ]. High-medium P i concentrations cause protein loss in myotubes from rat L6 cells and stimulate autophagy, resulting in myotube atrophy [ 337 ].…”
Section: Importance Of Dietary Phosphorus For Skeletal Muscle Heamentioning
confidence: 99%
“…On the other hand, hyperphosphatemia may contribute to the development of muscle weakness and frailty, at least in patients with CKD [ 335 , 336 ]. High-medium P i concentrations cause protein loss in myotubes from rat L6 cells and stimulate autophagy, resulting in myotube atrophy [ 337 ].…”
Section: Importance Of Dietary Phosphorus For Skeletal Muscle Heamentioning
confidence: 99%
“…Although the muscle physiology involved in hypophosphatemia has been studied for a long time, the effects of hyperphosphatemia on the homeostasis of skeletal muscle have not been fully elucidated. Recently, a human study by Chen et al [15] demonstrated an inverse association between serum phosphate levels and muscle strength. To the best of our knowledge, there is only one in vitro study that investigated the effect of high-phosphate conditions in mouse C 2 C 12 cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing occurrence of pathologic spontaneous activity was previously reported in mid-lactating dairy cows that were fed a P-deficient diet over a course of 5 wk (Grünberg et al, 2015b). Membrane instability developing in states of P deficiency may be attributable to disturbed synthesis of phospholipids that form an integral part of cell membranes that is well documented (Subramanian and Khardori, 2000;Chen et al, 2018). Dietary P supplementation over a course of 2 wk resulted in partial reversal of the observed effects of P deprivation on MUAP parameters, whereas the occurrence of pathologic spontaneous activity remained unchanged or even progressed during the repletion period of this study.…”
Section: Abmentioning
confidence: 93%
“…The observed correlations between plasma [Pi] and MUAP parameters at the end of the P-deprivation period indicate that the lower the plasma [Pi], the lower the number of functional muscle fibers. Indeed, several authors mention muscle cell membrane and structural integration disturbances as causes of myopathy noticed in hypophosphatemic patients (Bugg and Jones, 1998;Subramanian and Khardori, 2000;Chen et al, 2018). If muscle fibers do not contribute to the MUAP, the summation of the individual action potential parameters decreases, which is reflected in lower values of MUAP parameters such as MUAP amplitude or size index.…”
Section: Abmentioning
confidence: 99%